2014
DOI: 10.13005/msri/110109
|View full text |Cite
|
Sign up to set email alerts
|

Method Development and Validation for The Simultaneous Estimation of Levofloxacin and Cefpodoxime Proxetil by Using RP-HPLC in Combined Tablet Dosage Form

Abstract: An isocratic, reversed phase-liquid-chromatographic method was developed for the quantitative determination of Levofloxacin and Cefpodoxime proxetil in combined-dosage form. Alliance -Waters System with Agilant Zorbax Eclipse XBD-C8, (150mm×4.6; 5µm) column with mobile phase containing water with Ortho phosphoric acid: Methanol in the ratio of (80: 20, v/v) was used. The flow rate was 0.5 ml/min, column temperature was 40°C and effluents were monitored at 270 nm. The retention times of Levofloxacin and Cefpodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the literature survey it was found that Levofloxacin and Cefpodoxime were estimated in combination drugs by Spectrophotometric 5,6 and HPLC methods, [7][8][9] Levofloxacin Hemihydrate and Cefpodoxime Proxetil alone in tablet dosage form [10][11][12][13] . The plan of work is to develop a simple, sensitive, accurate and precise method for its analysis in combination drug formulation.…”
Section: Figure 2structure Of Cefpodoxime Proxetilmentioning
confidence: 99%
“…In the literature survey it was found that Levofloxacin and Cefpodoxime were estimated in combination drugs by Spectrophotometric 5,6 and HPLC methods, [7][8][9] Levofloxacin Hemihydrate and Cefpodoxime Proxetil alone in tablet dosage form [10][11][12][13] . The plan of work is to develop a simple, sensitive, accurate and precise method for its analysis in combination drug formulation.…”
Section: Figure 2structure Of Cefpodoxime Proxetilmentioning
confidence: 99%